Mutual commitment to support exchange: relation‐specific IT system as a substitute for managerial hierarchy - Kim, Sung Min; Mahoney, Joseph T. (Strategic Management Journal, 2006)
Abstract This paper examines the effects of information technology (IT) on the governance of vertically related firms. We propose that a highly relation‐specific IT system in inter‐firm transactions plays a key role in the resulting inter‐firm governance as a mutual sunk‐cost commitment, in terms of leading to both less vertical integration (i.e., a change in governance mode as a first‐order effect) and a smaller number of suppliers (i.e., a change within a governance mode as a second‐order effect). As a result, this highly relation‐specific IT system (bilateral investment) can be an alternative governance mode of electronic integration that acts as a substitute for managerial hierarchy and vertical financial ownership. From a strategic management perspective, this paper provides transaction costs and resource‐based explanations on IT systems' impact on the organizational boundary decision and its impact on the likelihood of the firm achieving sustainable competitive advantage. Copyright © 2006 John Wiley & Sons, Ltd.